ADVANTAGES AND RISKS OF TELEMEDICINE AND ONLINE MEDICAL SERVICES - Ganiev Nodirbek Abdulhamid oglu (Western European Studies, 2025)
This article analyzes the concept of medical service and its main aspects, identifies online services, which are a modern form of medical services, their types and main features. Information is provided about the functioning of online medical services and telemedicine on platforms in foreign countries, and about leading service platforms.
Keywords: medical service; telemedicine; law